Relationship Between Mercury Concentration in Water, Bottom Sediment And Two Mollusc Species (Crassostrea Gasar and Tympanotonus Fuscatus) From a Lagos Creek in Nigeria (Journal of Bio-Science, 2021)
Concentration of mercury was investigated in the flesh and shell of two species of benthic mollusc, Crassostrea gasar and Tympanotonus fuscatus and in water and sediment from Makoko Creek, adjacent to the Lagos Lagoon between January to September 2019. Values obtained for physicochemical parameters in Makoko Creek (water temperature- 28.92±0.1°C; pH- 7.73±0.02; salinity- 14.23±0.05 ppt; dissolved oxygen- 5.34±0.02 mg/l; biological oxygen demand- 7.780±0.1 mg/l and chemical oxygen demand- 12.34±0.02 mg/l) were within the acceptable levels for survival, metabolism and physiology of aquatic organism. The concentration of mercury followed decreasing order as sediment >water >flesh >shell across locations for both species. For all the tested samples of C. gasar and T. fuscatus, biowater accumulation factor in flesh and shell were higher than those of bio-sediment accumulation factor. The coefficients of variance (CV %) in shells were lower than those of the flesh for both investigated mollusc species. It was shown that mercury contents of flesh or shells of C. gasar and T. fuscatu are directly affected by those of water and bottom sediment.J. Bio-Sci. 29(1): 143-151, 2021 (June)